Immunomics: a 21st century approach to vaccine development for complex pathogens. Issue 2 (7th January 2016) - DE SOUSA, KARINA P.; DOOLAN, DENISE L.
SUMMARY: Immunomics is a relatively new field of research which integrates the disciplines of immunology, genomics, proteomics, transcriptomics and bioinformatics to characterize the host-pathogen interface. Herein, we discuss how rapid advances in molecular immunology, sophisticated tools and molecular databases are facilitating in-depth exploration of the immunome. In our opinion, an immunomics-based approach presides over traditional antigen and vaccine discovery methods that have proved ineffective for highly complex pathogens such as the causative agents of malaria, tuberculosis and schistosomiasis that have evolved genetic and immunological host-parasite adaptations over time. By using an integrative multidisciplinary approach, immunomics offers enormous potential to advance 21 st century antigen discovery and rational vaccine design against complex pathogens such as the Plasmodium parasite.